Effect of Puromycin and Actinomycin D on a Persistent Mumps Virus Infection In Vitro - Northrop, R. L. (1969)
Puromycin and actinomycin D were used to treat a line of human conjunctiva cells persistently infected with mumps virus (C-M cells) in order to determine where virus synthesis is inhibited. Although 90% of the cells in C-M cultures are infected, little or no infectious virus is produced by most cells in a growing culture. Adding puromycin to inhibit protein synthesis resulted in the production of infectious virus. Thus, all the viral proteins needed for virus completion were made in the growing cells. When actinomycin D was added to growing cells, infectious virus was again produced. Since mumps virus synthesis is actinomycin D-insensitive, this suggested a host control of the virus. Interferon was not detected. The possible mechanisms of host control are discussed.